Sustainable London? the future of a global city - Imrie, Rob 1958-; Lees, Loretta ca. 20./21. Jh (Policy Press, 2014)
An exploration of the rise of sustainable development policies in London by international authors. Essential reading for urban practitioners and policy makers, and students in social, urban and environmental geography, sociology and urban studies